2021
DOI: 10.1111/and.14101
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of reproductive function recovery after microsurgical varicocelectomy in men from infertile couples: Clinical and laboratory predictors

Abstract: The objective was to reveal predictors for fertility recovery after varicocelectomy in subfertile men. This retrospective study recruited 93 men with clinical varicocele and pathozoospermia who underwent microsurgical varicocelectomy. Stepwise discriminant analysis was performed to identify predictors of spontaneous pregnancy (SP) after surgery. ‘Clinically significant improvement’ (CSI) following varicocelectomy was defined as an increase in total progressively motile sperm count (TPMSC) by at least 12.5 mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Concerning pregnancies after varicocelectomy, most authors agree that an initial high TMSC leads to a higher chance of conception. 23 , 24 The same situation holds for sperm concentration. Different authors proposed different initial values of the sperm concentration (from 2 × 10 6 ml -1 to 20 × 10 6 ml −1 ) as a marker of varicocelectomy success.…”
Section: Comments To the Analysis And Limitationsmentioning
confidence: 78%
“…Concerning pregnancies after varicocelectomy, most authors agree that an initial high TMSC leads to a higher chance of conception. 23 , 24 The same situation holds for sperm concentration. Different authors proposed different initial values of the sperm concentration (from 2 × 10 6 ml -1 to 20 × 10 6 ml −1 ) as a marker of varicocelectomy success.…”
Section: Comments To the Analysis And Limitationsmentioning
confidence: 78%
“…Another critical predictor for fertility recovery is the increase of TPMSC post MSV. Shomarufov et al, [13] who conducted a retrospective study on 93 infertile men with varicocele and pathozoospermia who underwent MSV, also identi ed that postoperative increase in TPMSC were predictors of SP post surgery. Furthermore, they found that 50% of the treated patients had an increase in TPMSC by 12.5 million.…”
Section: Discussionmentioning
confidence: 99%
“…Shomarufov et al conducted a retrospective study on 93 infertile men with varicocele and pathozoospermia who underwent MSV. They identi ed age, initial total sperm motility, and postoperative increase in total progressively motile sperm count (TPMSC) as predictors of SP post-surgery [13]. Another retrospective study included 176 infertile patients treated with subinguinal MSV.…”
Section: Introductionmentioning
confidence: 99%
“…Another critical predictor for fertility recovery is the increase of TPMSC post MSV. Shomarufov et al, [ 14 ] who conducted a retrospective study on 93 infertile men with varicocele and pathozoospermia who underwent MSV, also identified that postoperative increase in TPMSC were predictors of SP post surgery. Furthermore, they found that 50% of the treated patients had an increase in TPMSC by 12.5 million.…”
Section: Discussionmentioning
confidence: 99%
“…Shomarufov et al conducted a retrospective study on 93 infertile men with varicocele and pathozoospermia who underwent MSV. They identified age, initial total sperm motility, and postoperative increase in total progressively motile sperm count (TPMSC) as predictors of SP post-surgery [ 14 ]. Another retrospective study included 176 infertile patients treated with subinguinal MSV.…”
Section: Introductionmentioning
confidence: 99%